WIRELESS SENSOR SYSTEM UNTUK PEMANTAUAN KADAR GAS AMONIA (NH3) MENGGUNAKAN ALGORITMA BERBASIS ATURAN - Arlien Siswanti; Suryono Suryono (Youngster Physics Journal, 2016)
Ammonia gas (NH3) is one of gas that causes air pollution. Ammonia gas (NH3) a colorless and has a very pungent is very dangerous if too much for by humans perhaps even cause of death. Wireless sensors system with the telemetry system can be solution measurements made from a distance. The study is done by making a wireless sensors system for monitoring levels ammonia gas (NH3) algorithm rule based as a limit exposure to the submission of the data use the network wifi. This system allows monitoring, recording levels of gas and early warning system ammonia gas from a distance. A system that created composed from sensors MQ-135 connected with mikrokontroler ATmega8535. The sensor reading is converted from analog to digital (ADC). Microrontroller ATmega8535 has USART feature (Universal Synchronous and Ansynchronous Serial Receiver dan Transmitter) as a serial communication mode. A communication system data using protocol RS232 to connect data serial communication to personal computer (PC). The results of the data acquisition sent to the station monitoring to technique telemetry use the network wifi that can be accessed in web browser on pc and to display in real-time presented in the form of table and saved to in a database. Testing system done by sending a number of data from field will be accepted by the monitoring stations. Several variables resulting from monitoring system that is date, time, temperature, moisture, levels of ammonia gas and health effects as a rule about the exposure ammonia gas. Result of the comparison between the data sent and received data has errors by 0% so that it can be ascertained no data is lost or gained. This suggests that the system going well.Keywords: Ammonia gas, MQ-135 sensor, Ruled base algorithm, Database, WiFi network.